Attitudes in Schools regarding Education for Global Citizenship - Ana Cristina Blasco-Serrano; Belén Dieste; Teresa Coma (Universidad Autónoma de Madrid, 2019)
In xxi century, education has the challenge of helping to people to understand the world and the other, in order to better understand oneself. In this framework, Education for Global Citizenship (ECG) is presented as an axis for social transformation. In this work, the experience of teaching teams in ECG practices is analyzed. The research carried out with educational teams of Primary and Secondary schools of the rural area of the province of Zaragoza is shown. The methodological design is a non-experimental descriptive study, taking as sample 77 schools, through a self-administered questionnaire. The two-stage cluster between the existence of coordinated ECG actions, the reasons for which they are developed, and the necessary aspects of improvement have highlighted three types of attitudes existing in the schools: passive, receptive and proactive, which become relevant when connected to the rest of the variables. The discussion points out the importance of sensitizing the entire educational community so that new proposals and initiatives are developed through planned, participatory and long-term projects. In this way, the attitude of teachers is a basic pillar, but institutional support will be essential to give stability to these proposals.